Influence of asphaltene on wax deposition: Deposition inhibition and sloughing. (15th April 2020) - Li, Huiyuan; Zhang, Jinjun; Xu, Qinggong; Hou, Chengyu; Sun, Yadong; Zhuang, Yu; Han, Shanpeng; Wu, Changchun
Highlights: Asphaltene inhibits wax deposit growth and causes an increase in the wax content. The asphaltene content of deposit constantly increases with time. The molecular weight and dipole moment of asphaltenes in deposits increase with time. The deposit sloughs off frequently when adding high asphaltene content in the oil. Abstract: Asphaltenes are the heaviest and most polar constituents of crude oils. The influences of asphaltene on wax deposition were investigated with model oils utilizing a Taylor-Couette device. The composition and rheological properties of the deposits and the chemical properties of the asphaltenes entrained in the deposits were analyzed. Three main observations were obtained: (a) Wax deposition rate decreases in the presence of asphaltenes while the wax content of the deposit increases. The carbon number distribution of the deposit and the critical carbon number of the deposition process were also observed to vary due to the presence of asphaltenes. (b) The asphaltene content of the deposit constantly increases as time elapses and eventually reaches several times higher than that of the original oil. The asphaltenes entrained in the deposits are of higher polarity and molecular weight than the asphaltenes originally present in the oil. (c) When the asphaltene content of the oil is above 0.2 wt%, deposits slough off frequently as asphaltenes alter the microstructure of the deposit and lower its yield strength.